O059 Efficacy and safety of embolo-sclerotherapy of arteriovenous malformation based on the experience from a single specialist centre. (22nd July 2022) - Pang, C; Arasakumar, DRB; Evans, N; Papadopoulou, A; Khalifa, M; Hamilton, G; Lim, CS; Brookes, J
Abstract: Introduction: To evaluate the efficacy and safety of EST, particularly foamed STS 3% in the treatment of arteriovenous malformations (AVMs) in a single specialist centre. Methods: All patients with AVMs who underwent EST from 01 January 2015–31 December 2019 were retrospectively reviewed. Types of AVM were grouped into Schobinger's classification. All ESTs were performed either with foam sclerosants (STS 3% and polidocanol), ethanol, coils and/or other substances including Onyx and Gelfoam. Outcome measures included treatment effects and complications. Continuous variables were compared using ANOVA F test. Other discrete variables were compared using Chi-squared tests. Differences were considered significant at p<0.05. Results: A total of 65 patients with AVMs, with a mean age of 36 years (range 1–74 years) were included. The age of patients with Type IV AVM were significantly (p=0.014) higher than others. The use of EST with foam STS was significantly lower for type IV AVM (0.0%) (p=0.003). Complications were significantly higher in type III AVM (21.1%)) (p=0.009). A total of 6 (9.2%) patients experienced complications for example, upper lip necrosis and partial facial weakness. The number of days in follow-up was not significantly different across all types of AVM. However, type II AVM showed a significantly lower number of days in follow-up (p=0.038). Conclusion: EST, in particular foam sclerotherapy with STS 3%, was clinically effective and safe to treat patients with AVM. This study showed that foam sclerotherapy with STS 3% may be used as an alternative to ethanol in the treatment of AVMs. Take-home message: EST, in particular foam sclerotherapy with STS 3%, was clinically effective and safe to treat patients with AVM. This study showed that foam sclerotherapy with STS 3% may be used as an alternative to ethanol in the treatment of AVMs.